Asthma and periodontal health in children - Davidović, Bojana; Ivanović, Mirjana; Bokonjić, Dejan; Janković, Svjetlana; Erić, Jelena; Lečić, Jelena (Vojnosanitetski pregled, 2021)
Background/Aim. Oral health is an important part of overall health. Good oral health is important for oral diseases prevention and health maintenance of respiratory system. The aim of the study was to evaluate oral hygiene and periodontal health parameters of asthmatic children and to compare them with children without asthma as well as to evaluate those parameters according to type of used medications and time of taking medications in children with asthma. Methods. This epidemiological study included 68 children with asthma and 68 children without asthma or any other chronic disease aged from 6 to 16 years. Parameters used in this study were Greene-Vermillion index, Löe-Silness gingival index and Community Periodontal Index (CPI). Results. Good oral hygiene (31.1%) was more present in children without asthma whereas poor hygiene (20.0%) was more frequent in children with asthma (p
Keywords: asthma; child; adolelscent; oral hygiene; periodontal index.